2017
DOI: 10.1186/s40900-016-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Learning to work together – lessons from a reflective analysis of a research project on public involvement

Abstract: Plain English summaryPatient and public involvement (PPI) in research is very important, and funders and the NHS all expect this to happen. What this means in practice, and how to make it really successful, is therefore an important research question. This article analyses the experience of a research team using PPI, and makes recommendations on strengthening PPI in research.There were different PPI roles in our study – some people were part of the research team: some were on the advisory group; and there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 10 publications
3
83
0
3
Order By: Relevance
“…Two publications supported the use of plain language and minimization of undefined acronyms and technical terms . Several publications also indicated that research projects should involve a diversity of patient perspectives, and that more than one patient partner should be invited to each project so that they could learn from and support each other . Projects should have a budget for engaging patient partners .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two publications supported the use of plain language and minimization of undefined acronyms and technical terms . Several publications also indicated that research projects should involve a diversity of patient perspectives, and that more than one patient partner should be invited to each project so that they could learn from and support each other . Projects should have a budget for engaging patient partners .…”
Section: Resultsmentioning
confidence: 99%
“…To integrate the emergent themes from the interviews with established concepts about PEIR, CBH selected 18 key publications related to PEIR from the scientific and grey literature (Table ) . These publications presented guiding principles, frameworks, models and recommendations relevant to engaging patients, communities, service users, stakeholders or the public in research . They were used in our analysis to supplement, confirm or refute the themes arising from the interviews.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, participants viewed as helpful the sense of mutuality and reciprocity. Peer instruction enhances participant engagement (Howe et al, ) and must be a central component in any PPI‐informed training. Furthermore, active engagement of all participants is key; otherwise, there is a real danger that participants may become passive recipients of yet another intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, participants viewed as helpful the sense of mutuality and reciprocity. Peer instruction enhances participant engagement (Howe et al, 2017) is of concern, as improving skill acquisition was a central feature of this PPI training intervention. Striking a balance between theoretical knowledge and practical skills has presented challenges in previous coproduced educational initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Research into PPI has mainly focused on the mechanisms of PPI, the varying perspectives on PPI and the motivations of the patients and public involved . A large body of research focuses on PPI in health research, particularly in more recent years. However, the specific role of patient and public involvement facilitators (PPIFs) remains under‐researched.…”
Section: Introductionmentioning
confidence: 99%